A parametric study on the graphical approach to assess corrosion vulnerability of concrete mixes in chloride environment. (22nd November 2021) - Baten, Bayezid; Manzur, Tanvir; Torsha, Tafannum; Alam, Shaurav
Highlights: Corrosion probabilities were quantified using probabilistic approach for durability assessment. Sixty concrete mixes with ranges of mix parameters and alternate binder contents were used. Characteristic distributions of relevant variables were considered to incorporate uncertainties. A dimensionless parameter was recommended to correlate with corrosion probabilities. Generalized graphical guidelines were developed for reliable estimation of corrosion risk. Abstract: Proper evaluation of corrosion risks is substantial for developing performance-based design guidelines which can ensure adequate durability of reinforced concrete structures in chloride prone environment. This study focused on a probabilistic approach to quantify and analyze corrosion vulnerability of a comprehensive mix range by incorporating uncertainties of multitudes of factors, which affect the chloride-induced corrosion phenomenon. Corrosion risks, in terms of corrosion probabilities, were evaluated for a wide range of cover values and target service live values of 60 concrete mixes while investigating the effect of different mix parameters (water to cementitious-materials (w/cm) ratios, target slump ranges, etc.). Inclusion of supplementary binders (fly-ash and slag), in replacement proportions of up to 40%, was also considered to investigate the effect of pozzolanic activity on corrosion probabilities. Profound correlations were also obtained between estimated corrosion probabilities and a convenient dimensionless parameter formulated from mix design parameters. The correlations were later implemented in developing generalised graphical guidelines which is deemed to be adept in quick and reliable estimation of tentative corrosion risks without conducting any destructive tests. This would also enable optimization of ideal binder type and mix design parameters while ensuring minimum corrosion risks for desired life-span.